Basic drawing apprenticeship through a vocation friendly methodology - Moutinho, Natacha Antão (2014)
This is an experience-based paper which addresses the importance of Drawing in formative disciplines of young students enrolled in fashion design courses, and present an innovative use for this basilar discipline in a Fashion Design Program. In this pedagogical approach we consider the implication of Drawing as interface and also acknowledge the important elements: conceptual operations; taxonomic icons; and drawing process, as interface components.